Pengaruh Perencanaan SDM terhadap Produktivitas Pegawai pada BPBD Kota Gunungsitoli - Otak Murni Gulo; Suka’aro Waruwu; Fatolosa Hulu; Otanius Laia (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2025)
Human resource planning is a process carried out by an organization to plan human resource needs and programs, so that organizational goals can be achieved. Proper human resource planning will result in good employee work productivity. The purpose of carrying out this research is: (1) To determine the effect of human resource planning on increasing employee work productivity at the Gunungsitoli City Regional Disaster Management Agency Office, (2) To find out how much influence human resource planning has on increasing employee work productivity at the Gunungsitoli City Regional Disaster Management Agency Office. The research location was carried out at the Gunungsitoli City Regional Disaster Management Agency Office. The research sample consisted of 33 people. Research result: (1) The results of the t test research can show that there is a positive and significant influence of human resource planning on work productivity variables at the Gunungsitoli City Regional Disaster Management Agency Office. According to the results of the t test, human resource planning (X) is 8,465 and its significance is 0,000. Hypothesis decision-making conditions are accepted or rejected based on their level of significance. If the significance is less than or equal to 0,05 then the hypothesis is accepted. The research results obtained a significance value of 0,000 < 0,05. Thus variable X (human resource planning) is statistically proven to have an effect on variable Y (work productivity). (2) According to the calculation of the coefficient of determination, the coefficient of determination obtained from the correlation of variable X and variable Y is 0,553, So it can be concluded that the size of the influence of variable X (human resource planning) on ​​variable Y (work productivity) is 55,3%.